BOTULINUM TOXIN TYPE A: MULTIFACETED THERAPY FOR NEUROLOGICAL, AUTONOMIC AND OCULAR DISORDERS - Katarzyna Jakubowska; Aleksander Białoń; Paweł Harbut; Dominika Walczak; Weronika Ewa Nowak; Adrian Kruk; Aleksandra Dorosz; Igor Gawłowski; Aleksandra Miśta; Lidia Jurczenko (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Botulinum toxin, a neurotoxin produced by Clostridium botulinum, is an effective form of therapy for treating conditions associated with excessive muscle activity or disorders of the autonomic nervous system. Its mechanism of action is based on the inhibition of acetylcholine release at presynaptic nerve terminals, leading to a reversible blockade of neuromuscular transmission and a subsequent reduction in muscle tone. This enables effective control of conditions such as dystonia, spasticity, chronic migraine, overactive bladder syndrome, strabismus, blepharospasm and nystagmus. Objective: The aim of this study is to present the current state of knowledge on the use of botulinum toxin in the treatment of dystonia, spasticity, chronic migraine, overactive bladder (OAB), strabismus, blepharospasm and nystagmus taking into account clinical efficacy and safety. Material and methods: A review of the literature available in PubMed, Scopus, and Web of Science databases was conducted, including randomized clinical trials, meta-analyses, and scientific society guidelines. Results: Botulinum toxin type A (BoNT-A) is a recognized and safe therapeutic intervention for the treatment of neurological and autonomic disorders such as dystonia, spasticity, chronic migraine, and neurogenic overactive bladder. In patients with dystonia and spasticity, BoNT-A reduces muscle tone, limits involuntary contractions, and alleviates pain, supporting rehabilitation and preventing contractures. In chronic migraine, the therapy reduces both the frequency and severity of pain attacks, while in neurogenic overactive bladder, it alleviates urinary urgency and incontinence. In the treatment of strabismus, it enables correction of muscle imbalance and improvement of eye alignment. In blepharospasm, it reduces the frequency and strength of eyelid spasms. In nystagmus, it reduces the amplitude of eye tremors and improves fixation stability. Numerous studies indicate that BoNT-A is also effective in cases resistant to standard treatment, with the safety and effectiveness of the therapy depending on individual dose adjustment and systematic monitoring of clinical effects. Conclusions: Botulinum toxin type A (BoNT-A) is an effective and safe therapy for the treatment of neurological and autonomic disorders such as spasticity, dystonia, chronic migraine, neurogenic overactive bladder, strabismus, blepharospasm and nystagmus. The use of BoNT-A leads to symptom relief, pain reduction, and improved quality of life for patients, especially in cases resistant to conventional treatment, while maintaining a favorable safety profile through individualized adjustment and monitoring of clinical effects.